Assessment of causal associations among gut microbiota, metabolites, and celiac disease: a bidirectional Mendelian randomization study - Li, Ting; Feng, Yan; Wang, Chun; Shi, Tian; Abudurexiti, Adilai; Zhang, Mengxia; Gao, Feng (Frontiers in Microbiology, 2023)
Background A growing number of studies have implicated that gut microbial abundance and metabolite concentration alterations are associated with celiac disease (CD). However, the causal relationship underlying these associations is unclear. Here, we used Mendelian randomization (MR) to reveal the causal effect of gut microbiota and metabolites on CD. Methods Genome-wide association study (GWAS) summary-level data for gut microbiota, metabolites, and CD were extracted from published GWASs. Causal bacterial taxa and metabolites for CD were determined by two-sample MR analyses. The robustness of the results was assessed with sensitivity analyses. Finally, reverse causality was investigated with a reverse MR analysis. Results Genetically, increased genus Bifidobacterium was potentially associated with higher CD risk (odds ratio [OR] = 1.447, 95% confidence interval [CI]: 1.054–1.988, p = 0.022) while phylum Lentisphaerae (OR = 0.798, 95% CI: 0.648–0.983, p = 0.034) and genus Coprobacter (OR = 0.683, 95% CI: 0.531–0.880, p = 0.003) were related to lower CD risk. Moreover, there were suggestive associations between CD and the following seven metabolites: 1-oleoylglycerophosphoethanolamine, 1-palmitoylglycerophosphoethanolamine, 1,6-anhydroglucose, phenylacetylglutamine, tryptophan betaine, 10-undecenoate, and tyrosine. Sensitivity analyses deemed the results reliable without pleiotropy. Conclusion We investigated the causal relationships between gut microbiota, metabolites, and CD with two-sample MR. Our findings suggest several novel potential therapeutic targets for CD treatment. Further understanding of the underlying mechanism may provide insights into CD pathogenesis.